PALEOTEMPERATURE INTERPRETATION BASED ON CALCAREOUS NANNOPLANKTON OF KEDUNG SUMBER RIVER SECTION, SOKO, BOJONEGORO, EAST JAVA - Siti Umiyatun Choiriah; Carolus Prasetyadi; Rubiyanto Kapid; Dwi Fitri Yudiantoro; Muhammad Syaifudin (Techno LPPM, 2020)
Analysis of 64 samples taken from the Kedung Sumber River section represent of Kalibeng Formation, Atasangin Member, Klitik Member, Sonde Formation, and Pucangan Formation. The detail of nannoplankton analysis showing that temperature changes influenced to the growth of nannoplankton.  Result of this study reveals that a number of 32 zones paleotemperature change. Age of the Kalibeng Formation is Late Miocene to Early Pliocene (NN10-NN13), divided into nine zones: 1/warm, 2/cold, 3/transitional, 4/warm, 5/cold, 6/warm, 7/cold, 8/cold, 9/warm zone. Atasangin Member are divided into 3 zones: 10/cold, 11/warm, 12/cold zone. Age of this member is Early Pliocene (NN13-NN14). Klitik Member is Early Pliocene to Late Pliocene (NN14-NN17), and divided to 7 zones: 13/transitional, 14/warm, 15/cold, 16/warm, 17/cold, 18/warm zone. Age of Sonde Formation is NN18-NN20 (Late Pliocene to Early Pleistocene), have into 7 zones: 19/cold, 20/warm, 21/transitional, 22/cold, 23/transitional, 24/cold, 25/transitional, 26/ cold, 27/transitional zone, 28/warm, 29/cold zone. Pucangan Formation are divided into 3 zones: 30/warm, 31/transitional, 32/cold zone. Age of this formation is Pleistocene (NN20-NN21).